2017
DOI: 10.2147/cia.s134760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a giant exercising board game intervention on ambulatory physical activity among nursing home residents: a preliminary study

Abstract: PurposeThis study examined the effects of a giant (4×3 m) exercising board game intervention on ambulatory physical activity (PA) and a broader array of physical and psychological outcomes among nursing home residents.Materials and methodsA quasi-experimental longitudinal study was carried out in two comparable nursing homes. Ten participants (aged 82.5±6.3 and comprising 6 women) meeting the inclusion criteria took part in the 1-month intervention in one nursing home, whereas 11 participants (aged 89.9±3.1 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 58 publications
3
36
0
10
Order By: Relevance
“…An overview of the findings about the effects of board games and programs that use board games on other conditions is shown in Table 3 [7, 8, 3436]. This category addressed the impacts of board games on physical activity, anxiety, ADHD symptoms, and the severity of Alzheimer’s Disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the findings about the effects of board games and programs that use board games on other conditions is shown in Table 3 [7, 8, 3436]. This category addressed the impacts of board games on physical activity, anxiety, ADHD symptoms, and the severity of Alzheimer’s Disease.…”
Section: Resultsmentioning
confidence: 99%
“…The “other studies” category in the present review included five studies that examined the effects of board games on physical activity, physical and psychological outcomes, ADHD symptoms, and the severity of Alzheimer’s Disease. Mouton et al [34] showed that a giant board game intervention for nursing home residents led to significant increases in ambulatory physical activity, daily energy output, quality of life, balance and gait, and ankle strength. The effect sizes in the present review of studies related to physical activity ranged from very small to medium.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that playing AVGs over short periods of time is similar to light-to-moderate physical activities (Biddiss & Irwin, 2010;Wagener et al, 2012). Interventions using a giant exercising board game showed a signi cant increase in ambulatory PA among nursing home residents (Mouton et al, 2017), so maybe it can be effective in promoting PA among families.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that costs or lack of money, insufficient awareness of the benefits of physical activities, distance from gyms, transportation restrictions and dependence on others for getting around, and lack of time are among the main factors keeping the elderly from taking part in physical activities; and that gaining health, maintaining and improving physical fitness, pleasure and joy, social interactions, and controlling stress are among the top motivators for the elderly to engage in physical activities 22. Mouton et al made use of games to improve motion and physical activities in the elderly, and they observed that the elderly would gradually engage in exercise sessions with more independence and enthusiasm 25. Thus, physical activities that are enjoyable and are performed in a group can act as an incentive to encourage the elderly to regularly participate in them.…”
Section: Introductionmentioning
confidence: 99%